2019
DOI: 10.1016/j.athoracsur.2018.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Administration of Olive Oil Reduces Chylothorax After Minimally Invasive Esophagectomy

Abstract: Background. Chylothorax after esophagectomy is uncommon but potentially fatal. We performed a retrospective study to assess the effect of olive oil administered orally before surgery on reducing chylothorax in patients who underwent minimal invasive esophagectomy.Methods. Between May 2013 and December 2016, patients with esophageal squamous cell cancer who underwent minimal invasive esophagectomy were screened. Patients in the investigational group were preoperatively administered olive oil orally 8 hours befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…According to our experience, routine thoracic duct ligation was recommended for middle or upper esophageal cancer with T3-T4, and should be performed when thoracic duct was damaged de nitely or suspiciously. In addition, several studies found that preoperative oral administration of olive oil can effectively pevent chylothorax [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…According to our experience, routine thoracic duct ligation was recommended for middle or upper esophageal cancer with T3-T4, and should be performed when thoracic duct was damaged de nitely or suspiciously. In addition, several studies found that preoperative oral administration of olive oil can effectively pevent chylothorax [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…20 Oral administration of olive oil 8 hours before esophagectomy might also be effective to minimize postoperative chylothorax. 21 Similarly, preoperative oral administration of milk facilitates visualization of the thoracic duct and decreases the risk of iatrogenic injury during esophagectomy. 22 Preventive octreotide was not associated with a reduced risk of chylothorax after mediastinal lymph node dissection.…”
Section: Discussionmentioning
confidence: 99%
“…60,61 However, the contrast provided is low with poor reproducibility. 62 NIR-ICG technique is an important clinical tool for intraoperative assessment of unidentified TD injury providing a precise method for identification of chyle leakage site with excellent sensitivity and specificity. Additionally, it provides real-time visual confirmation of the stoppage of the leak, seen as the accumulation of green fluorescence at the site of ligation/clipping.…”
Section: Thoracic Duct (Td) Mappingmentioning
confidence: 99%